Efficient Capture and Reversible Storage of Radioactive Iodine by Porous Graphene with High Uptake. Issue 36 (25th September 2018) - Sun, Hanxue; Mu, Peng; Xie, Huimin; Zhu, Zhaoqi; Liang, Weidong; Zhou, Zhifang; Li, An
Abstract: The demand for the safe and efficient capture and storage of radioactive iodine is growing worldwide especially after the Fukushima accident. Herein, porous graphene materials, which were prepared by reduction of graphene oxide followed by chemical activation, are proposed for removal and storage of iodine. The effect of activation on the structure and porosity of the porous graphene was characterized. Owing to its high accessible space for iodine uptake, an iodine vapor adsorption capacity of 4110 mg g −1 was achieved, which is the highest value for solid carbon‐based adsorbents up to now. Quite different from that of adsorption of iodine vapor, the adsorption of iodine from solvent solution is less affected by the porosity of porous graphene. The adsorption kinetic data can be well represented by the pseudo‐second‐order model and the equilibrium data can be defined well to the Langmuir isotherm. These findings may offer not only a simple and efficient new approach for trapping harmful and radioactive iodine species by carbon materials, but also provide fundamental insight into the structure‐activity relationship of graphene materials for iodine adsorption. Abstract : Herein, porous graphene materials are proposed for the removal and storage of iodine from both vapor and solution phases. Owing to the high accessible space for iodine uptake, an adsorption capacity of 4110 mg g −1 was achieved for porous graphene, which was the highest value for solid carbon‐based adsorbents up to now, making them promising candidates for large‐scale industrial radioiodine capture and environment remediation in the future.